2003
DOI: 10.1128/jvi.77.24.12980-12985.2003
|View full text |Cite
|
Sign up to set email alerts
|

VariedImmunity Generated in Mice by DNA Vaccines with Large and SmallHepatitis DeltaAntigens

Abstract: Hepatitis delta virus (HDV) is a defective single-stranded RNA virus. The assembly and transmission of HDV require a supply of hepatitis B surface antigen (HBsAg) from hepatitis B virus (HBV) (21, 25). HDV superinfection can lead to fulminant hepatic failure and also has a high probability of progressing to chronic hepatitis or cirrhosis (8,22,24,27,28). Furthermore, HDV superinfection can increase the risk of hepatocellular carcinoma and mortality in patients with HBVrelated cirrhosis (6). Although the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Various immunologic mechanisms contributed to the modeling of HDV population. In our previous study, DNA-based immunization could lead the endogenous small HDAg to generate a significantly higher anti-HDV response than the large HDAg (11). Epitope mapping further showed that the peptide from aa 174 to 195 could bind more strongly with antibodies induced by the DNA vaccine expressing the small HDAg than those induced by the DNA vaccine expressing the large HDAg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various immunologic mechanisms contributed to the modeling of HDV population. In our previous study, DNA-based immunization could lead the endogenous small HDAg to generate a significantly higher anti-HDV response than the large HDAg (11). Epitope mapping further showed that the peptide from aa 174 to 195 could bind more strongly with antibodies induced by the DNA vaccine expressing the small HDAg than those induced by the DNA vaccine expressing the large HDAg.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell and T-cell epitopes were mapped based on in vitro studies (16,25). Recently, we reported two potential cytotoxic T-cell epitopes in animal and in vitro studies (10,11). We reported that HDV variants in quasispecies might be changed during clinical course of chronic hepatitis D (29).…”
mentioning
confidence: 99%
“…Interestingly, we also previously characterized S-HDAg sequences in HDV-infected patients on a high-dose interferon treatment regimen and found that the 169 to 172 aa domain was hypervariable and might represent an important selected epitope after 1 year of interferon therapy, when the replication recurred (P. DĂ©ny, unpublished data). The discrepancy observed between the patient Ab response against these 2 regions (Table 1) might also be associated with the level of expression of each HDAg isoform: in a mouse model, using vaccination with plasmids expressing S-HDAg, L-HDAg, or a nonfarnesylated form of L-HDAg-C 211 S mutant, it was suggested that the L-HDAg vaccination response hardly reacted with epitope aa 174 to 194, in contrast to the S-HDAg or L-HDAg C 211 S mutant vaccination responses (31).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of modern vaccine design is to induce significant HDV-specific CTL responses. Our previous studies showed that HDV DNA vaccine produced Th1 and CTL responses in a mouse model [15,16]. HDV DNA vaccine can modify the course of HDV infection in a woodchuck model [17].…”
Section: Introductionmentioning
confidence: 98%